Rural citizen-patient priorities for healthcare in British Columbia, Canada: findings from a mixed methods study - Jude Kornelsen; Christine Carthew; Kayla Míguez; Matilda Taylor; Catherine Bodroghy; Kathryn Petrunia; Delia Roberts (BMC, 2021)
Abstract Background The challenge of including citizen-patient voices in healthcare planning is exacerbated in rural communities by regional variation in priorities and a historical lack of attention to rural healthcare needs. This paper aims to address this deficit by presenting findings from a mixed methods study to understand rural patient and community priorities for healthcare. Methods We conducted a provincial survey of rural citizens-patients across British Columbia, Canada to understand their most pressing healthcare needs, supplemented by semi-structured interviews. Survey and interview participants were asked to articulate, in their own words, their communities' most pressing healthcare needs, to explain the importance of these priorities to their communities, and to offer possible solutions to address these challenges. Open-text survey responses and interview data were analyzed thematically to elicit priorities of the data and their significance to answer the research questions. Results We received 1,287 survey responses from rural citizens-patients across BC, 1,158 of which were considered complete. We conducted nine telephone interviews with rural citizens-patients. Participants stressed the importance of local access to care, including emergency services, maternity care, seniors care, specialist services and mental health and substance use care. A lack of access to primary care services was the most pronounced gap. Inadequate local health services presented geographic, financial and social barriers to accessing care, led to feelings of vulnerability among rural patients, resulted in treatment avoidance, and deterred community growth. Conclusions Two essential prongs of an integration framework for the inclusion of citizen-patient voices in healthcare planning include merging patient priorities with population needs and system-embedded accountability for the inclusion of patient and community priorities.